الأبعاد الثقافية في السرد النسوي لرواية -امرأة من طابقين- "لهيفاء بيطار" نموذجا - صنية خليفة (My University, 2023)
Summary I conducted a study in this research in women’s narrative, particularly focusing on Haifa Bitar. This thesis can be summarized as an exploration of women’s narrative and the various cultural, social, and psycholigical dimensions within the novel. I also presented some examples of female creativity historically, culturally, and within an islamic context. I also delved into understanding the concept of women’s narrative and its characteristics. In conclusion, I noticed that feminist literature is a significant topic as it addresses women’s issues and exposes the reality of a male-dominated society characterized by violence, oppression, and racism. Through my study of a novel and its analysis, I observed that it reflects the personality of an educated, attractive, and ambitious woman who always seeks to highlight her femininity through her creative writing. ------------------------ قمت في هذا البحث بدراسة موضوع الأبعاد الثقافية في السرد النسوي. لهيفاء بيطار وقد تلخصت هذه المذكرة في التعرف على السرد النسوي ومختلف الأبعاد الثقافية والاجتماعية والنفسية في الرواية ثم تعرضت لبعض النماذج في الإبداع الأنثوي تاريخيا وثقافيا واسلاميا وتطرقت أيضا إلى التعرف إلى مفهوم السرد النسوي وخصائصه. وفي الأخير لاحظت أن السرد النسوي هو موضوع لأنه يهتم بقضايا المرأة ويكشف لها حقيقة المجتمع الذكوري الذي يتميز بالعنف والقهر والعنصرية فمن خلال دراستي لرواية وتحليلها لاحظت أنها تعكس شخصية المرأة المثقفة الجذابة الطموحة التي تسعى دائما إلى إبراز ذاتها الأنثوية من خلال إبداعاتها في الكتابة. ----------------------- J’ai mené cette recherche sur l’étude des dimensions culturelles dans la narration féminine. Il s’agit d’une mémoire qui vise à comprendre la narration féminine et les différentes dimensions culturelles, sociales et psychologiques dans le roman. Ensuite, j’ai présenté quelques exemples de la créativité féminine sur le plan historique, culturel et islamique. J’ai également abordé la définition du concept de la narration féminine et ses caractéristiques. C’est une observation intéressante. Le récit féminin peut en effet servir de moyen pour explorer et dénoncer les problèmes auxquels les femmes sont confrontées dans une société caractérisée par la violence, l’oppression et le racisme. Il peut également mettre en lumière la personnalité de la femme éduquée, séduisante et ambitieuse, qui cherche constamment à affirmer sa féminité à travers ses créations littéraires.